Understanding the underlying systems dynamics contributing to the continued predominance of the unhealthy motorway food environment in the Netherlands: identifying leverage points and actions for change - Lisanne Geboers; Coosje Dijkstra; Frédérique C. Rongen; Sanne K. Djojosoeparto; Maartje P. Poelman (BMC Medicine)
Abstract Background Motorway food environments are dominated by roadside restaurants and petrol station stores offering predominantly unhealthy quick-service meals and foods for on-the-go consumption. Improving these environments to promote healthier diets is necessary, but how to achieve this is not fully understood. Therefore, this study aims to identify the complex underlying systems dynamics contributing to the continued predominance of the unhealthy motorway food environment as well as to identify potential leverage points and corresponding actions for change to improve the healthiness of the motorway food environment. Methods Two Group Model Building workshops were held in October 2023 with motorway food environment stakeholders (e.g. food providers, producers, national policymakers, truck drivers). In the first workshop, a Causal Loop Diagram (CLD) was created to identify the system that contributes to the continued predominance of the unhealthy motorway food environment. The research team then identified leverage points for change based on the CLD. During the second workshop, stakeholders formulated actions to improve the motorway food environment for each identified leverage point. Leverage points and actions were classified based on the Action Scales Model (ASM). Results The resulting CLD comprised six interconnected subsystems (food providers, supply chain collaboration, government, social culture, road users, global trends) with six reinforcing feedback loops, underlying the continued predominance of the unhealthy motorway food environment. Additionally, 14 potential leverage points and 31 corresponding actions for change were identified at different levels of the system based on the ASM (i.e. events, structures, goals and beliefs). Conclusions The findings show many interrelated factors and mechanisms underlying the continued predominance of the unhealthy motorway food environment. Actions for change were proposed together with stakeholders aimed at leverage points at different system levels. The results show that the motorway food environment is shaped by broader societal goals and beliefs (e.g. the profitability of unhealthy products) and social-cultural beliefs particularly evident to the on-the-go setting, including the motorway food environment. Together they present the strongest potential for leveraging systems change. There is a need for a coherent multidimensional action plan targeting these leverage points, which is broadly supported by various stakeholders, to induce systemic change.